Structural insights into the interaction of botulinum neurotoxin a with its neuronal receptor SV2C. (February 2020) - Li, Xiaodan; Brunner, Cyrill; Wu, Yufan; Leka, Oneda; Schneider, Gisbert; Kammerer, Richard A.
Abstract: A dual-receptor interaction with a polysialoganglioside and synaptic vesicle glycoprotein 2 (SV2) is required for botulinum neurotoxin A (BoNT) toxicity. Here, we review what is currently known about the BoNT/A-SV2 interaction based on structural studies. Currently, five crystal structures of the receptor–binding domain (Hc) of BoNT subtypes A1 and A2 complexed to the large luminal domain (LD4) of SV2C have been determined. On the basis of the available structures, we will discuss the importance of protein-protein and protein-carbohydrate interactions for BoNT/A toxicity as well as the high plasticity of BoNT/A for receptor recognition by tolerating a variety of side-chain interactions at the interface. A plausible explanation how receptor-binding specificity of BoNT/A may be achieved without an extensive and conserved side chain-side chain interaction network will be provided. Highlights: BoNT/A and SV2C interact through open β-strands in a manner similar to amyloid-fibril formation. Protein-protein and protein-glycan interactions with SV2C are important for BoNT/A toxicity. SPR measurements raise questions concerning the contribution of receptor N-glycosylation to toxin binding. BoNT/A shows high plasticity for the interaction with SV2C. Specificity of BoNT binding to SV2C is achieved through shape complementarity.